Analysis of Factors Affecting the Quality of Internal Audits in the Indonesian Government Sector: A Case Study of the Inspectorate of the Ministry of the State Secretariat - Fransiskha Mersyani; Susanto Salim (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study aims to analyze the effects of competence, independence, time-budget pressure, and workload on the quality of internal audits within the Inspectorate of the Ministry of the State Secretariat. Research Method: This study employed a quantitative approach with a causal design. Primary data were collected through a questionnaire distributed to all 41 internal auditors using census sampling. The data were analyzed using multiple linear regression with IBM SPSS Statistics 31. Results and Discussion: The study indicates that competence and independence have a significant positive effect on the quality of internal audits, whereas time budget pressure has a significant negative effect. Workload shows a negative relationship but does not have a significant effect. These findings suggest that the quality of internal audits is determined more by the auditors’ professional capacity and the effectiveness of assignment execution. Implications: The research findings provide input to strengthen the competencies, independence, and time management of APIP personnel to improve the quality of internal audits. Originality: This study expands the application of Agency Theory by examining the determinants of internal audit quality at APIPs within central government ministries, which have institutional characteristics distinct from those of local government inspectorates.